Statistical Inter-stimulus Interval Window Estimation for Transient Neuromodulation via Paired Mechanical and Brain Stimulation - Kim, Euisun; Meinhold, Waiman; Shinohara, Minoru; Ueda, Jun (Frontiers in Neurorobotics, 2020)
3 For achieving motor recovery in individuals with sensorimotor deficits, augmented activation of 4 the appropriate sensorimotor system and facilitated induction of neural plasticity are essential. 5 An emerging procedure that combines peripheral nerve stimulation and its associative stimulation 6 with central brain stimulation is known to enhance the excitability of the motor cortex. In order to 7 effectively apply this paired stimulation technique, timing between central and peripheral stimuli 8 must be individually adjusted. There is a small range of effective timings between two stimuli, or 9 the inter-stimulus interval window (ISI-W). Properties of ISI-W from neuromodulation in response 10 to mechanical stimulation (Mstim) of muscles have been understudied because of the absence of 11 a versatile and reliable mechanical stimulator. This paper adopted a combination of transcranial 12 magnetic stimulation (TMS) and Mstim by using a high-precision robotic mechanical stimulator. 13 A pneumatically operated robotic tendon tapping device was applied. A low-friction linear cylinder 14 achieved high stimulation precision in time and low electromagnetic artifacts in physiological 15 measurements. This paper describes a procedure to effectively estimate an individual ISI-W from 16 the transiently enhanced motor evoked potential (MEP) with a reduced number of paired Mstim 17 and sub-threshold TMS trials by applying statistical sampling and regression technique. This paper 18 applied a total of four parametric and nonparametric statistical regression methods for ISI-W 19 estimation. The developed procedure helps to reduce time for individually adjusting effective ISI, 20 reducing physical burden on the subject.